Pengelolaan dan Pengembangan Agroindustri Tahu Rumahan Di Desa Sialang Sakti Kecamatan Dayun, Kabupaten Siak - Indah Fauziah; Agus Nasrulloh; Fahmi Fadillah; Kepriasari A. R.; Firman Dwi Nugraha; Vontinesa Amanda; Adilah Qurrotu Aini; Diana Isnaini Siregar; Ghina Nurjannah (Kuras Institute & Scidac Plus, 2022)
Sialang Sakti is one of the villages located in Dayun District, Siak Regency, Riau, Indonesia which has an area of ​​about 1,915 hectares. Sialang Sakti Village consists of 6 RW and 20 RT. The majority of the population in Sialang Sakti village make a living as farmers. Based on data from the village, the number of farmers is about 548 people, followed by the livelihoods of farm laborers around 138 people and the number of traders, both home and market traders around 40 people. The most widely cultivated agricultural commodity is oil palm. However, various production businesses in the village have begun to enter the stage of development that is under the guidance of the village business. Including in the home-based tofu production business which is mostly done by the local community. Soybean is the main ingredient in the management of this tofu production. In an effort to get soybeans, the village cooperates with several soybean sales agents to get good choices of soybeans. Therefore, the purpose of service by Kukerta Unri Students is in terms of managing and developing tofu businesses in the village. The methods used are surveys, collaboration, practice and training. The results obtained are in the form of good, savory and delicious tofu and the results of sales or marketing as income for the local community.